Análisis de las cuentas por cobrar en CNEL EP. Los Ríos periodo 2022 – 2023. - Gaibor Nivela, Dayana Lisbeth (2024)
Accounts receivable management consists of planning, organizing, directing and monitoring credit policies in order to ensure the necessary existence of assets in a company. When the administration of these accounts is not carried out properly, it can generate negative consequences at an administrative and financial level. The objective of the investigation is to analyze the accounts receivable of the company CNEL EP in the province of Los Ríos for the period 2022-2023, through the review of the entity's information. The study had a mixed approach, the types of research applied are: bibliographic and field. On the other hand, the techniques used are: documentary analysis and interview, so it was necessary to use an interview questionnaire and the calculation of financial ratios as an instrument. The results of the investigation allowed us to conclude that: The level of accounts receivable in CNEL EP Unit of the province of Los Ríos is high, for the period 2022 the accounts pending collection from the public and private sector corresponded to $54,019,412.71, which clearly shows that they are very high values; while in the 2023 period there was a reduction in accounts receivable, but not significantly since the values still exceed fifty million dollars.